Penerapan Nilai-Nilai Aksiologis oleh Kepala Sekolah TK Pembina 1 Penajam terhadap Etika Kerja Guru dan Karakter Anak - Agus Santosa; Anita Dwi Basuki; Muh. Amir Masruhim (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to analyze the application of axiological values in the leadership of the principal of Kindergarten Handayani 1 Penajam and its impact on teachers’ work ethic and children’s character development. A qualitative case study approach was employed. Data were collected through in-depth interviews, participatory observations, and document analysis involving the principal, teachers, parents, and learning activities. Data were analyzed using the interactive model of Miles and Huberman with triangulation to ensure data validity. The findings reveal that the principal’s value-based leadership, emphasizing integrity, empathy, justice, and moral responsibility, contributes to the creation of a humanistic and inclusive school culture. This leadership approach positively affects teachers’ work ethic, reflected in improved discipline, professionalism, and commitment. Furthermore, the integration of axiological values through daily habituation and school–community collaboration supports holistic character development in children, including religious values, honesty, discipline, independence, responsibility, and self-confidence. The study concludes that axiological-based leadership is essential for sustaining educational quality and fostering comprehensive character development in early childhood education.